Bogdan Schipor, Politica Marii Britanii la frontiera de vest a Uniunii Sovietice: 1938-1941 - Silviu Miloiu (Revista Română pentru Studii Baltice şi Nordice, 2009)
As a professor of Baltic and Nordic studies, I consider this book as marking a progress in our knowledge of British policy in the area and in the East European states’ policies of enlisting British help to their independence strivings and, therefore, I strongly recommend this book to both specialist and non-specialist Romanian and foreign readers.